APPLICATION OF INCLUSION EDUCATION IN EARLY CHILDREN'S ISLAMIC RELIGION LEARNING - Abidin, Muhammad Zainal; Tin Warotul Fatimah (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2024)
Islam is one of the fields of study that must be taught by teachers in formal education institutions. Therefore, Islamic religious learning is an effort to teach various religious issues and values. This research is based on the existence of religious education for children which often fails, because religious education has so far emphasized cognitive and affective aspects, paying less attention to the psychomotor domain. The aim of this research is to describe in depth the application of inclusive education in early childhood Islamic religious learning with aspects of faith, worship and morals at the Pelangi Anak Negeri Yogyakarta Islamic Kindergarten. This research method is qualitative. The data is collected by observing, interviewing and documenting. Data analysis uses data reduction, data presentation, drawing conclusions and testing the validity of the data using technical triangulation. Research results: (1) The implementation of inclusive education serves the needs of students regardless of all differences, which can be seen from the principles of learning, using a curriculum that is modified according to student needs, class composition consisting of various aspects of diversity , Islamic religious learning develops aspects: aqidah, namely introducing God, worship by performing prayers , murajaah , reading Iqra, and morals by teaching the words sorry, thank you , please; (2) Supporting factors for implementing inclusive education are: Human Resources (HR) and parents . Meanwhile, the inhibiting factors are: school buildings, Special Guidance Teachers (GPK), and teachers in handling Children with Special Needs (ABK).